The Economic and Political situations in Diyarbakir In light of the travel books of the Ottoman era - هەروتی, سەعدی عوسمان (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The city of Diyarbakir (Amade) was a large city and center of an Ottoman Vilayet in the Ottoman era, and it was located on one of the main transport routes. So many of the travelers visited it, including: the Ottoman travelers (Evliya Celebi/ the mid-17th century) & (Ali bek/ the second half of the 19th century). And the French traveler (Jean Otter), who visited the city in 1743. As well as (Kinneir/ 1813) and (William Heude/ 1817) which they comes from England. Also the tow Americans (Horatio Sawthgate) and (Asahel Grant), whom traveled to Diyarbakir in 1839. In addition to the (Soan/ 1907) of England, and others. In this research, we attempted to shed light on the economic and administrative-political situations in Diyarbakir during the Ottoman period, using the information of those travelers. At the beginning of the research, we identified the travelers who have benefited from their books. Then we discussed the economic situation; which included: agriculture & animal husbandry, crafts, the works of the population, as well as trade routes and exchanges. At the end of the research, we presented information on the administrative - political situation of Diyarbakir.